Method for researching influence of interface space charge on insulation electrical strength
By preparing the equivalent tablet sample of the soft joint interface and using electron beam irradiation technology to accurately control the injection of space charge, combined with DC breakdown testing, the problem of difficulty in evaluating the impact of space charge distribution in the insulating layer of the soft joint on the insulating electrical strength is solved in the prior art, and a systematic study of the space charge distribution of the soft joint interface and the optimization of the insulating electrical performance are achieved.
Patent Information
- Application Number
- CN202510080374.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to effectively evaluate the impact of space charge distribution in the insulating layer of soft joints on the electrical strength of insulation, and it is impossible to achieve a systematic study on the space charge of the interface of full-size cable soft joints.
By preparing soft joint interface equivalent tablet samples, and using electron beam irradiation technology to accurately control the injection depth and quantity of space charges, the influence of space charge on insulating electrical strength was studied in combination with DC breakdown test.
A systematic study on the spatial charge distribution of different positions and quantities of soft joint interfaces is realized, providing a scientific basis for the optimization of the electrical performance of soft joint insulation, reducing the research cost and experimental difficulty.
Smart Images

Figure CN119902035A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrical insulation, and in particular to a method for studying the influence of interface space charge on insulation electrical strength. Background Art
[0002] The transmission of renewable energy is inseparable from the high-voltage submarine cable system. As the equipment for transmitting electricity in offshore wind power, submarine cables have an important impact on the safety and stability of offshore power transmission. The open sea has high requirements for the continuous long-distance production, transportation and laying capabilities of submarine cables. For transmission distances exceeding the maximum continuous production length, flexible joints become the main means to increase the distance.
[0003] Submarine cable flexible joints are made by welding copper conductors, restoring the inner shield, restoring the insulation layer, and restoring the outer shield, etc., from the inside to the outside of two cables to achieve each layer of connection, so that the mechanical and electrical performance indicators of the connection are consistent with those of the cable body. However, due to the limitations of the actual production process, the performance at the interface of the flexible joint often cannot reach the level of the insulation of the body. There are many types of defects at the interface of the flexible joint, such as interface pores, accumulation of cross-linked byproducts, and molecular chain breaks. These defects can easily become traps for capturing space charges under a DC electric field, resulting in the accumulation of space charges at the interface and causing insulation electric field distortion.
[0004] At present, there is no effective means to evaluate the influence of the space charge distribution in the flexible joint insulation layer on the electrical strength of the flexible joint insulation. There are many feasible technical means for measuring the space charge distribution in the insulation layer of full-size cables, such as electroacoustic pulse method, laser pressure wave method, and thermal pulse method. However, the testing of full-size cables often consumes huge costs and time, and the existing space charge distribution measurement methods cannot achieve non-destructive measurement, and the cable needs to be pre-processed. Therefore, the measurement duration of the space charge distribution in the full-size cable is usually short, and the measured space charge accumulation is small. During the test phase, the cable insulation does not show obvious performance degradation. Therefore, this type of method cannot determine whether the accumulated space charge in the long-term operation environment will affect the electrical strength of the cable insulation. In addition, there is little research on the space charge at the interface of the actual full-size cable flexible joint at this stage, and no accurate rules have been found for the injection and distribution characteristics of the space charge near the flexible joint interface. In practical applications, the sources of space charge in cable insulation are different. It may be injected from the shielding layers on both sides, or it may come from the dissociation of impurity molecules such as by-products, which makes the space charge distribution in the insulation layer uneven and random in spatial position and quantity. Existing methods for measuring space charge distribution cannot systematically study the effects of space charges at different locations and in different quantities within the flexible joint insulation layer on the insulation electrical strength. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a method for studying the influence of space charges distributed at the interface of a flexible joint on the electrical strength of insulation. The method can realize the fixed-point and quantitative injection of space charges in an equivalent pressed sheet at the interface of the flexible joint, and systematically study the influence of space charge distribution at different spatial positions and different quantities in the flexible joint insulation on the electrical strength and other properties of the flexible joint insulation, thereby providing guidance for the suppression of space charges at the interface of the flexible joint in the actual process.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for studying the effect of interfacial space charge on insulation electrical strength comprises the following steps:
[0008] Prepare equivalent tabletting samples of soft joint interfaces;
[0009] The soft joint interface equivalent pressed sheet sample is subjected to electron beam irradiation, and space charge is injected to obtain the irradiated soft joint interface equivalent pressed sheet sample;
[0010] A DC breakdown test was carried out on the equivalent pressed sheet samples of the irradiated soft joint interface to study the effect of the interface space charge on the insulation electrical strength.
[0011] Furthermore, the preparation of the flexible joint interface equivalent pressed sheet sample includes separately preparing a body insulation equivalent pressed sheet sample and a recovery insulation equivalent pressed sheet sample with a thickness of x, and stacking them to form a flexible joint interface equivalent pressed sheet sample with a thickness of 2x.
[0012] Further, the preparation of the bulk insulation equivalent pressed sheet sample with a thickness of x includes pressing the insulating particles into a bulk insulation pressed sheet with a thickness of x, vulcanizing and vacuum degassing the bulk insulation pressed sheet to obtain the bulk insulation equivalent pressed sheet sample;
[0013] The preparation of the restored insulation equivalent pressed sheet sample with a thickness of x comprises pressing the insulating particles into a restored insulation pressed sheet, the area and thickness of which are the same as those of the bulk insulation equivalent pressed sheet sample, to obtain the restored insulation equivalent pressed sheet sample;
[0014] The method for making a flexible joint interface equivalent pressed sheet sample with a thickness of 2x includes stacking a main insulation equivalent pressed sheet sample and a recovery insulation equivalent pressed sheet sample, pressing them into a single pressed sheet sample, vulcanizing and vacuum degassing the single pressed sheet sample, and obtaining a flexible joint interface equivalent pressed sheet sample with a thickness of 2x.
[0015] Furthermore, in the preparation step of the body insulation equivalent pressed sheet sample, the pressing temperature of the insulating particles is 110-130°C, the pressure is 10-20MPa, the vulcanization temperature is 170-190°C, the pressure is 10-20MPa, and the vacuum degassing temperature is 70-90°C, and the time is 10-15 hours; in the preparation step of the recovery insulation equivalent pressed sheet sample, the pressing temperature of the insulating particles is 110-130°C, the pressure is 10-20MPa; in the preparation step of the flexible joint interface equivalent pressed sheet sample with a thickness of 2x, the pressing temperature is 110-130°C, the pressure is 10-20MPa, the vulcanization temperature is 170-190°C, the pressure is 10-20MPa, and the vacuum degassing temperature is 70-90°C, and the time is 10-15 hours.
[0016] Furthermore, when injecting the space charges, the injection depth and quantity of the space charges are controlled by adjusting the acceleration energy, beam flow rate and irradiation time of the electron beam.
[0017] Furthermore, the acceleration energy of the electron beam is greater than 40 keV.
[0018] When the irradiation energy is lower than 40keV, electrons are easily dissipated from the irradiated surface, resulting in increased instability of the charge amount. When the irradiation energy is greater than 40keV, the spatial charge injection position and quantity are accurately controlled, with a deviation of less than 10%, and the scheme has high stability.
[0019] Furthermore, the method for injecting space charge comprises the following steps:
[0020] The equivalent pressed sheet sample of the soft joint interface is subjected to electron beam irradiation, the acceleration energy is adjusted to control the injection depth of the space charge, and the electron beam flow rate and irradiation time are adjusted to control the injection amount of the space charge;
[0021] After irradiation, the samples were packaged with aluminum foil and plastic film and stored frozen at -20--5℃.
[0022] Furthermore, the acceleration energy and irradiation time are calibrated by electron beam irradiation using a bulk insulation equivalent pressed sheet sample with a thickness of 2x.
[0023] Furthermore, the calibration method comprises the following steps:
[0024] The electron acceleration energy E1 when the injection depth is x is calculated according to the following formula (1), and the electron beam irradiation time t1 is calculated according to the injection charge quantity q1 specified in the experimental plan and the beam flow rate I1 of the irradiation equipment. The acceleration energy E1 and the electron beam irradiation time t1 are used to perform electron beam irradiation on a bulk insulation equivalent pressed sheet sample with a thickness of 2x;
[0025]
[0026] q=It (2)
[0027] Where r (in meters) is the depth of space charge injection; E0 (in MeV) is the acceleration energy of the electron; ρ (in g / cm 3 ) is the density of the irradiated sample; α, β, and γ are constants of 0.55 g / cm 2 MeV -1 , 0.9841, 3MeV -1 ; q (unit: C) is the amount of injected charge; I is the beam flux of the irradiated electron beam; t is the irradiation time;
[0028] After the irradiation is completed, the bulk insulation equivalent pressed sheet sample is placed in a spatial charge distribution measuring device for spatial charge distribution measurement, and the difference between the actual charge injection depth r and the quantity q and the x and q1 in the design scheme of step (i) is compared. If the deviation between the two does not exceed 10% of the design value of the experimental scheme, the flexible joint interface equivalent pressed sheet sample is subjected to electron beam irradiation according to the electron beam acceleration energy E1 and the electron beam irradiation time t1 of step (i); if the actual charge distribution deviation exceeds this range, the electron beam acceleration energy and the electron beam irradiation time need to be adjusted so that the calibrated bulk insulation equivalent pressed sheet sample meets the requirements; wherein, the charge injection depth r is the distance between the starting position of the spatial charge packet in the measurement result and the irradiated upper surface, and the charge quantity q is the product of the integral area of the spatial charge peak and the irradiated area.
[0029] Furthermore, the method for adjusting the electron beam acceleration energy in step (ii) is as follows: if the actual charge injection depth is less than 10% of the design value of the experimental scheme, the acceleration energy is increased step by step by 5keV, and the actual spatial charge distribution position is measured in sequence until the actual spatial charge distribution depth meets the design value requirement; if the actual charge injection depth is greater than 10% of the design value of the experimental scheme, the acceleration energy is reduced step by step by 5keV, and the actual spatial charge distribution position is measured in sequence until the actual spatial charge distribution depth meets the design value requirement;
[0030] The method for adjusting the electron beam irradiation time is as follows: if the actual charge injection amount is less than 10% of the experimental design value, the irradiation time is increased, and the theoretical charge amount change value (q=It) adjusted each time does not exceed 1×10 -9 C, after adjustment, measure and calculate the actual charge injection amount until it meets the design value requirements; if the actual charge injection amount is greater than 10% of the design value of the experimental scheme, shorten the irradiation time, and according to the beam flow rate of the electron beam irradiation device, the theoretical charge amount change value (q = It) adjusted each time shall not exceed 1×10 -9C, after adjustment, measure and calculate the actual charge injection amount until it meets the design value requirements.
[0031] Furthermore, the method of conducting a DC breakdown test on the irradiated flexible joint interface equivalent pressed sheet sample to study the influence of interface space charge on the insulation electrical strength includes: placing the irradiated flexible joint interface equivalent pressed sheet sample in a DC breakdown device for electrical insulation strength test, and comparing the DC breakdown strength with the non-irradiated flexible joint interface equivalent pressed sheet sample under the same sample preparation conditions, and comparing the influence of space charge distribution at different positions and with different amounts on the electrical strength of the flexible joint interface equivalent pressed sheet sample.
[0032] Furthermore, the DC breakdown test uses ball-to-ball electrodes, and the insulation side of the body is used as the high-voltage side for testing.
[0033] The present invention also provides the application of the method for studying the influence of interface space charge on insulation electrical strength in cable material development and power equipment performance testing.
[0034] Furthermore, the method for studying the influence of interfacial space charge on insulation electrical strength can be particularly applied to optimizing the improvement of interface insulation electrical performance of high-voltage cables and high-voltage submarine cable flexible joints.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention provides a method for studying the influence of space charge on the electrical strength of insulation at the interface of a flexible joint, which has significant technical advantages and application value. First, the preparation method of an equivalent pressed sample is adopted to effectively reduce the cost and experimental difficulty of studying the interface characteristics of the flexible joint, and avoid the high cost and high complexity test of the full-size cable. Secondly, combined with the electron beam irradiation technology, by precisely controlling the acceleration energy and beam flow of the electron beam, the space charge can be quantitatively and point-injected, thereby realizing the study of the space charge distribution at different positions and quantities of the flexible joint interface. This method not only has high precision and high stability, but also can simulate the space charge distribution that may exist in actual operation on the sample, thereby providing a scientific basis for the optimization of the electrical strength of the flexible joint insulation. Further, through the DC breakdown test, the influence of space charge on the insulation performance of the flexible joint can be intuitively evaluated, and the influence mechanism of different charge distributions on the electrical strength of the insulating material can be revealed, which provides guidance for the design and process improvement of cables and their accessories. In addition, the method of the present invention can be widely used in the development of cable materials and the performance detection of power equipment, has important engineering application value and market prospects, can promote the technological progress of electrical insulation materials, and improve the safety and reliability of power systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1This is the sample preparation process of the equivalent tabletting of the flexible joint interface in Example 1.
[0038] Figure 2 The spatial charge distribution in the bulk insulating sample of Example 2 is calibrated when the acceleration energy is 50 keV.
[0039] Figure 3 The spatial charge distribution in the bulk insulating sample is calibrated when the acceleration energy is 60 keV in Example 3.
[0040] Figure 4 This is the spatial charge distribution in the interface sample of the body insulating surface irradiation test when the acceleration energy is 60 keV in Example 4.
[0041] Figure 5 This is the spatial charge distribution in the interface sample of the body insulating surface irradiation test when the acceleration energy is 80 keV in Example 5.
[0042] Figure 6 This is the spatial charge distribution in the interface sample of the main insulating surface irradiated when the acceleration energy is 40 keV in Example 6.
[0043] Figure 7 This is the restoration of the spatial charge distribution within the interface sample of the insulating surface irradiation test when the acceleration energy is 35 keV in Example 7.
[0044] Figure 8 These are the DC breakdown test results of the irradiated and non-irradiated samples of Example 4. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It is worth noting that the methods used in the present invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercially available products unless otherwise specified, and their sources are not specifically limited.
[0046] Example 1
[0047] This embodiment provides a method for preparing a soft joint interface equivalent tabletting sample, comprising the following steps:
[0048] (i) Under the conditions of 120° C. and 15 MPa, the insulating particles are pressed into a circular bulk insulating sheet using a mold with an area of s and a thickness of x, and then the sample is vulcanized at 180° C. and 15 MPa without taking out the sample, and degassed at 80° C. under vacuum for 12 hours to obtain a bulk insulating equivalent pressed sheet sample;
[0049] (ii) at 120° C. and 15 MPa, using a die with an area of s and a thickness of x, the insulating particles are pressed into a circular restored insulating sheet, the area and thickness of which are the same as those of the bulk insulation equivalent pressed sheet sample, to obtain a restored insulating equivalent pressed sheet sample;
[0050] (iii) Using a mold with an area of s and a thickness of 2x, the main insulation equivalent pressed sheet sample and the recovery insulation equivalent pressed sheet sample are stacked, and pressed into a single round sheet sample at 110-130°C and 10-20MPa, and then vulcanized at 170-190°C and 10-20MPa, and degassed at 70-90°C under vacuum for 10-15 hours to obtain a soft joint interface equivalent pressed sheet sample with a thickness of 2x.
[0051] The preparation process of the equivalent compression sample of the soft joint interface is as follows: Figure 1 shown.
[0052] Example 2
[0053] At 120°C and 15MPa, the insulating particles were pressed into a circular bulk insulating sheet using a mold with an area of s and a thickness of 0.4mm. The sample was then vulcanized at 180°C and 15MPa without removing it, and degassed at 80°C under vacuum for 12 hours to obtain a bulk insulating equivalent pressed sheet sample, which was then irradiated with an electron beam. The bulk insulating equivalent pressed sheet sample was about 388μm thick, the irradiation energy was 50keV, the electron beam current was 1nA, and the irradiation time was 10s. Finally, 9.17×10 -9 C electrons, with a theoretical injection depth of 43.1 μm and a theoretical injection volume of 1×10 -8 C deviation does not exceed 10%.
[0054] Example 3
[0055] At 120°C and 15MPa, the insulating particles were pressed into a circular bulk insulating sheet using a mold with an area of s and a thickness of 0.4mm. The sample was then vulcanized at 180°C and 15MPa without removing it, and degassed at 80°C under vacuum for 12 hours to obtain a bulk insulating equivalent pressed sheet sample, which was then irradiated with an electron beam. The bulk insulating equivalent pressed sheet sample was about 390μm thick, the irradiation energy was 60keV, the electron beam current was 1nA, and the irradiation time was 10s. Finally, 9.7×10 -9 C electrons, with a theoretical injection depth of 59.5 μm and a theoretical injection volume of 1×10 -8 C deviation does not exceed 10%.
[0056] Example 4
[0057] According to the method of Example 1, a 160 μm thick flexible joint interface equivalent pressed sheet sample was prepared, and the sample was subjected to electron beam irradiation. The irradiated surface was the insulating surface of the bulk, the irradiation energy was 60 keV, the electron beam current was 1 nA, and the irradiation time was 12 s. Finally, about 1.2×10 -8 C electrons, with a theoretical injection depth of 59.5 μm and a theoretical injection volume of 1.2×10 -8 The deviation of C does not exceed 10%. The spatial charge distribution in the sample is as follows Figure 4 The DC breakdown strength test was performed on the unirradiated soft joint interface equivalent pressed sheet sample and the irradiated soft joint interface equivalent pressed sheet sample (spherical electrode, with the insulating side of the sample body as the high voltage side). The breakdown strength of the unirradiated sample was about 421.9 kV / mm, and the breakdown strength of the irradiated sample was about 399.1 kV / mm. The electrons accumulated near the interface will reduce the DC breakdown strength of the sample. The DC breakdown test results of the irradiated and unirradiated samples are shown in Figure 8 shown.
[0058] Example 5
[0059] According to the method of Example 1, a 200 μm thick flexible joint interface equivalent pressed sheet sample was prepared, and the sample was subjected to electron beam irradiation. The irradiated surface was the insulating surface of the bulk, the irradiation energy was 70 keV, the electron beam current was 1 nA, and the irradiation time was 20 s. Finally, about 1.8×10 -8 C electrons, with a theoretical injection depth of 78.1 μm and a theoretical injection volume of 2×10 -8 The deviation of C does not exceed 10%. The spatial charge distribution in the sample is as follows Figure 5 The DC breakdown strength test was performed on the unirradiated soft joint interface equivalent pressed sheet sample and the irradiated soft joint interface equivalent pressed sheet sample (spherical electrode, with the insulating side of the sample body as the high voltage side). The breakdown strength of the unirradiated sample was about 416.5 kV / mm, and the breakdown strength of the irradiated sample was about 382.6 kV / mm. The electrons accumulated near the interface will reduce the DC breakdown strength of the sample.
[0060] Example 6
[0061] According to the method of Example 1, a 200 μm thick flexible joint interface equivalent pressed sheet sample was prepared, and the sample was subjected to electron beam irradiation. The irradiated surface was the bulk insulating surface, the irradiation energy was 40 keV, the electron beam current was 1 nA, and the irradiation time was 5 s. Finally, about 4.6×10 -9C electrons, with a theoretical injection depth of 29.0 μm and a theoretical injection volume of 5×10 -9 The deviation of C does not exceed 10%. The spatial charge distribution in the sample is as follows Figure 6 The DC breakdown strength test was performed on the unirradiated soft joint interface equivalent pressed sheet sample and the irradiated soft joint interface equivalent pressed sheet sample (spherical electrode, with the sample body insulation side as the high voltage side), where the breakdown strength of the unirradiated sample was about 420.7kV / mm, and the breakdown strength of the irradiated sample was about 406.1kV / mm. The electrons accumulated in the insulation area of the body will reduce the DC breakdown strength of the sample.
[0062] Example 7
[0063] According to the method of Example 1, a 150 μm thick soft joint interface equivalent pressed sheet sample was prepared, and the sample was irradiated with an electron beam, the irradiated surface was the restored insulating surface, the irradiation energy was 35 keV, the electron beam current was 1 nA, and the irradiation time was 5 s. Finally, about 2.9×10 -9 C electrons, the space charge distribution within the sample is as follows Figure 7 As shown. When the irradiation energy is low, electrons are easy to dissipate from the irradiated surface, and the actual injected charge distribution is unstable, with a significant deviation from the theoretical value. In addition, due to the limitation of the measurement resolution of the space charge measurement device, the electron signal peak injected by irradiation is easy to overlap with the electrode induced charge peak, affecting the judgment of the actual electron distribution position and quantity. The DC breakdown strength test was performed on the unirradiated soft joint interface equivalent pressed sheet sample and the irradiated soft joint interface equivalent pressed sheet sample (spherical electrode, with the insulating side of the sample body as the high voltage side). The breakdown strength of the unirradiated sample was about 430.1kV / mm, and the breakdown strength of the irradiated sample was about 436.4kV / mm. The electrons accumulated in the recovery insulating area will enhance the DC breakdown strength of the sample.
[0064] The technical means of performing fixed-point positioning distribution of space charge by electron beam irradiation technology proposed in the present invention can effectively reduce the research cost and realize a systematic study on the influence of space charge distribution at different positions and in different quantities on the electrical strength of the soft joint interface in the equivalent pressed tablet sample of the soft joint interface. When the irradiation energy is greater than 40keV, the position and quantity of space charge injection are accurately controlled, the deviation is less than 10%, and the scheme is highly stable.
[0065] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for studying the effect of interfacial space charge on insulation electrical strength, comprising the following steps: Prepare equivalent tabletting samples of soft joint interfaces; Electron beam irradiation is performed on the soft joint interface equivalent pressed sheet sample, and space charge is injected to obtain the irradiated soft joint interface equivalent pressed sheet sample; A DC breakdown test was carried out on the equivalent pressed sheet samples of the irradiated soft joint interface to study the effect of the interface space charge on the insulation electrical strength.
2. The method according to claim 1, characterized in that: The preparation of the flexible joint interface equivalent pressed sheet sample comprises separately preparing a bulk insulation equivalent pressed sheet sample and a recovery insulation equivalent pressed sheet sample each having a thickness of x, and stacking them to form a flexible joint interface equivalent pressed sheet sample with a thickness of 2x.
3. The method according to claim 2, characterized in that: The preparation of the bulk insulation equivalent pressed sheet sample with a thickness of x comprises pressing the insulating particles into a bulk insulation pressed sheet with a thickness of x, vulcanizing and vacuum degassing the bulk insulation pressed sheet to obtain the bulk insulation equivalent pressed sheet sample; The preparation of the restored insulation equivalent pressed sheet sample with a thickness of x comprises pressing the insulating particles into a restored insulation pressed sheet, the area and thickness of which are the same as those of the bulk insulation equivalent pressed sheet sample, to obtain the restored insulation equivalent pressed sheet sample; The method for making a flexible joint interface equivalent pressed sheet sample with a thickness of 2x includes stacking a main insulation equivalent pressed sheet sample and a recovery insulation equivalent pressed sheet sample, pressing them into a single pressed sheet sample, vulcanizing and vacuum degassing the single pressed sheet sample, and obtaining a flexible joint interface equivalent pressed sheet sample with a thickness of 2x.
4. The method according to claim 3, characterized in that: When the insulating particles are pressed into a main insulating pressed sheet with a thickness of x, the pressing temperature of the insulating particles is 110-130°C.
5. The method according to claim 3, characterized in that: When the insulating particles are pressed into a main insulating pressed sheet with a thickness of x, the pressing pressure of the insulating particles is 10-20 MPa.
6. The method according to claim 3, characterized in that: The vulcanization temperature of the main body insulating sheet is 170-190°C.
7. The method according to claim 3, characterized in that: The vulcanization pressure when the main body insulating sheet is vulcanized is 10-20MPa.
8. The method according to claim 3, characterized in that: When the main body insulating sheet is vulcanized and vacuum degassed, the temperature of the vacuum degassing is 70-90°C.
9. The method according to claim 3, characterized in that: When the main body insulating sheet is vulcanized and vacuum degassed, the vacuum degassed time is 10-15 hours.
10. The method according to claim 3, characterized in that: The pressing temperature when the insulating particles are pressed into the restored insulating pressed sheets is 110-130°C.
11. The method according to claim 3, characterized in that: The pressing pressure when the insulating particles are pressed into the restored insulating pressed sheets is 10-20 MPa.
12. The method according to claim 3, characterized in that: The pressing temperature when the single tablet sample is pressed is 110-130°C.
13. The method according to claim 3, characterized in that: The compression pressure when the single tablet sample is compressed is 10-20 MPa.
14. The method according to claim 3, characterized in that: When a single pressed sheet sample is vulcanized, the vulcanization temperature is 170-190°C.
15. The method according to claim 3, characterized in that: When a single pressed sample is vulcanized, the vulcanization pressure is 10-20 MPa.
16. The method according to claim 3, characterized in that: When a single pressed sample is vulcanized and vacuum degassed, the vacuum degassing temperature is 70-90°C.
17. The method according to claim 3, characterized in that: When a single compressed sample is vulcanized and vacuum degassed, the vacuum degassed time is 10-15 hours.
18. The method according to claim 1, characterized in that: When injecting the space charges, the injection depth and quantity of the space charges are controlled by adjusting the acceleration energy, beam flow rate and irradiation time of the electron beam.
19. The method according to claim 18, characterized in that: The acceleration energy of the electron beam is greater than 40 keV.
20. The method according to claim 18, characterized in that: The method for injecting space charge comprises the following steps: (i) performing electron beam irradiation on the equivalent pressed sheet sample of the soft joint interface, adjusting the acceleration energy to control the injection depth of the space charge, and adjusting the electron beam flux and irradiation time to control the injection amount of the space charge; After irradiation, the samples were packaged with aluminum foil and plastic film and stored frozen at -20--5℃.
21. The method according to claim 20, characterized in that: The acceleration energy and irradiation time are calibrated by electron beam irradiation using a bulk insulation equivalent pressed sheet sample with a thickness of 2x.
22. The method according to claim 21, characterized in that: The calibration method comprises the following steps: The electron acceleration energy E1 when the injection depth is x is calculated according to the following formula (1), and the electron beam irradiation time t1 is calculated according to the following formula (2) and the injection charge quantity q1 specified in the experimental plan and the beam flow rate I1 of the irradiation equipment. The acceleration energy E1 and the electron beam irradiation time t1 are used to perform electron beam irradiation on a bulk insulation equivalent pressed sheet sample with a thickness of 2x; q=It (2) Where r (in meters) is the depth of space charge injection; E0 (in MeV) is the acceleration energy of the electron; ρ (in g / cm 3 ) is the density of the irradiated sample; α, β, and γ are constants of 0.55 g / cm 2 MeV -1 , 0.9841, 3MeV -1 ; q (unit: C) is the amount of injected charge; I is the beam flux of the irradiated electron beam; t is the irradiation time; After the irradiation is completed, the bulk insulation equivalent pressed sheet sample is placed in a spatial charge distribution measuring device for spatial charge distribution measurement, and the difference between the actual charge injection depth r and the quantity q and the x and q1 in the design scheme of step (i) is compared. If the deviation between the two does not exceed 10% of the design value of the experimental scheme, the flexible joint interface equivalent pressed sheet sample is subjected to electron beam irradiation according to the electron beam acceleration energy E1 and the electron beam irradiation time t1 of step (i); if the actual charge distribution deviation exceeds this range, the electron beam acceleration energy and the electron beam irradiation time need to be adjusted so that the calibrated bulk insulation equivalent pressed sheet sample meets the requirements; wherein, the charge injection depth r is the distance between the starting position of the spatial charge packet in the measurement result and the irradiated upper surface, and the charge quantity q is the product of the integral area of the spatial charge peak and the irradiated area.
23. The method according to claim 1, characterized in that: The method of conducting a DC breakdown test on an irradiated flexible joint interface equivalent pressed sheet sample to study the influence of interface space charge on the electrical strength of insulation comprises: placing the irradiated flexible joint interface equivalent pressed sheet sample in a DC breakdown device to conduct an electrical insulation strength test, and comparing the DC breakdown strength with that of an unirradiated flexible joint interface equivalent pressed sheet sample under the same sample preparation conditions, and comparing the influence of space charge distribution at different positions and with different amounts on the electrical strength of the flexible joint interface equivalent pressed sheet sample.
24. The method according to claim 1, characterized in that: The DC breakdown test uses ball-to-ball electrodes and uses the insulation side of the body as the high-voltage side for testing.
25. Application of the method for studying the influence of interfacial space charge on insulation electrical strength as described in any one of claims 1 to 24 in cable material development and power equipment performance testing.